Peran Abdul Haris Nasution dalam Pembebasan Irian Barat (1957-1962) - Devi Nurhikmi; Ajid Thohir; Samsudin Samsudin (Historia Madania: Jurnal Ilmu Sejarah, 2020)
This article seeks to describe one of the Dutch-Indonesian conflict, the liberation of West Irian. The focus of this study is the role of Abdul Haris Nasution in the Liberation of West Irian in 1957-1962. The method used in this study is historical research method which is carried out through four stages: heuristic, criticism, interpretation, and historiography. Abdul Haris Nasution’s role in this event was taking over Dutch companies, establishing the National Front for the Liberation of West Irian (FNPIB) and becoming its chairman, also TNI diplomacy by buying weapons and mision abroad to hear other countries’ responses regarding West Irian.